Tangible Video Communication 1 - Yang, Fan (2016)
Tangible virtual communication provides a touch sensor in conventional audio and visual communication methods to make humans communicate in a more immersive environment. Currently, 3D and Virtual Reality technologies are widely used in entertainment and construction areas. The solid idea of this project is to provide a tangible channel for virtual communication. This project aims to identify the methods that can actualize this purpose by using haptic devices, and research on how an independent tangible channel can be established and used along with existing video communication applications.